Understanding Nanjing City Image Communication in China’s National News Media: A Cultural Discourse Analysis Perspective (Sinología hispánica. China Studies Review, 2020)
City image communication is of high significance for city marketing and city competitiveness enhancement. The article explores the interaction between news discourse and Nanjing city image communication. Literature review: Most of studies focus on city architecture, tourism and landscapes and public security. However, less attention has been paid to the relations between discourse and city image communication. Research questions: 1. Who is speaking to communicate Nanjing city image?2. What kind of image of Nanjing is communicated? 3. How or in what way is Nanjing city imagecommunicated? Methodology: The study adopts a fusion of the perspectives of constructivism andcultural discourse studies (CDS) to account for Nanjing city image communication in political and culturalcontexts of contemporary China. Results: (1) the voices of ordinary professionals and citizens in thenews narration reflect the trend of diversity in discourse subjects;(2) Nanjing city image are constructedfrom four aspects, governing style, economic development, environmental protection, history, culture& education, with the negative topic of corruption, bribery and air/water pollution; (3) Nanjing cityimage are communicated favorably by news stories of event profiles and general picture profiles, givingus a portrait of Nanjing mostly by describing hot issues and introducing policies. Conclusions: The mediadiscourse of Nanjing city image is a reflection of social changes and realities, working as a catalyst toshape people’s views toward Nanjing’s reality and to mold the practice of the communication. Thestudy contributes to city image communication by developing an interdisciplinary discursive frameworkand provides Implications for city administrators and communicative strategists, professionals in citymarketing and professional communication theorist in constructing and communicating city image.